Long-term stable disease with mFOLFOX6 chemotherapy plus cetuximab for bone marrow metastasis from rectal cancer: A case report - Fan, Xiumei; Li, Fang; Xiao, Chong; Cai, Yi; You, Fengming (Frontiers in Oncology, 2023)
Bone marrow metastasis from rectal cancer is a rare but severe disease associated with a poor prognosis due to limited treatment options. There is no consensus on therapeutic strategies, and better-tolerated and more effective treatment options are urgently needed. We report a case that one patient with rectal cancer developed pancytopenia 15 months after completion of radical surgery and chemotherapy and was diagnosed with bone marrow metastasis. The patient was treated with mFOLFOX6 chemotherapy plus cetuximab, considering both his poor bone marrow function and a genetic test showing a wild-type of KRAS/NRAS/PIK3CA/BRAF. Twelve cycles were successfully completed with dose modifications and supportive measures. The patient’s condition improved markedly based on a comprehensive assessment that included computed tomography images, blood cell counts, tumor markers, and clinical symptoms. The patient remains alive for 11 months at the last follow up. The patient treated with mFOLFOX6 chemotherapy plus cetuximab attained long-term stable disease, suggesting its promising efficacy and safety for bone marrow metastasis from rectal cancer and may hold promise as a treatment strategy for this specific patient population. Consideration can be given to the inclusion of mFOLFOX6 chemotherapy plus cetuximab in first-line treatment regimen for bone marrow metastasis from rectal cancer.